The Effect of Dialysis Environment On High Flux Dialysis Membranes - Aksoy, M. E.; Usta, M.; Ucisik, A. H. (Springer-Verlag Berlin, 2007)
Due to their clinical outcomes high flux dialysis membranes have been widely used within the last decade. In this study the effect of dialysis environment on the new generation high flux dialyzers containing polysulphone were investigated. The material properties of these new generation dialyzers were monitored. Dialysis sessions were performed on a certain group of patients with dialysis age less than two years and without any other accompanying disease. It is shown that collection microscopical, mechanical data and XRD (X-Ray Diffraction) results revealed the differences in material characteristics between virgin and used membranes produced of new generation membrane materials like polysulphone. With the help of tensile testing it has been shown that the mechanical properties virgin membranes were reduced by 60% in terms of elongation and by 26% in terms of stress. Depending on the XRD experiments performed it has been shown that crystallinity of the polysulphone dialysis membranes have raised [1]. SEM (Scanning Electrone Microscopy) studies helped us in showing the morphological changes of dialysis membranes after dialysis sessions. It has been concluded that high flux dialyzer membranes are getting more brittle due to decreased mechanical properties and increased crystallinity. This issue is very important for dialysis centers performing reuse procedures for dialysis centers, because any damage to dialysis membranes would cause very serious clinical complications.
World Congress on Medical Physics and Biomedical Engineering -- AUG 27-SEP 01, 2006 -- Seoul, SOUTH KOREA
Keywords: High flux Hemodialysis; Polysulphone; Tensile testing; X-Ray Diffraction; Dialyzer